Performance Analysis of Islamic Micro Finance Institutions on Sustainable Rural Development in Indonesia - Aan Zainul Anwar; Edi Susilo; Fatchur Rohman; Purbayu Budi Santoso; Edy Yusuf Agung Gunanto; Darwanto Darwanto (Journal of Finance and Islamic Banking, 2020)
This study aims to analyze the influence of the performance of Islamic microfinance institutions (MFIs) in strengthening the agricultural and fisheries sector to realize sustainable rural development. The study uses quantitative method and purposive sampling method. The sample of this study was 85 agricultural and fishery business actors in Central Java, Indonesia. The variable quality of service, accessibility and philanthropic characteristics of Islamic MFIs towards sustainable rural development which mediated by strengthening of the agricultural and fisheries sector. The urgency of this research is to establish a financing model for the agriculture and fisheries sector. This study uses primary data which collected through filling out the questionnaires by business actors in the agriculture and fisheries sector. The results showed that 1) the service quality of Islamic MFIs had no impact on strengthening the agricultural and fisheries sector 2) accessibility of Islamic MFIs had a positive impact on strengthening the agricultural and fisheries sector 3) philanthropic characteristics had a positive impact on strengthening the agricultural and fisheries sector 4) strengthening the agriculture and fisheries sector has a positive impact on sustainable rural development. This research can be used as a model for channeling customer funds to finance Islamic MFIsÂ